Sports Lodges in the Ottoman Empire Depicted in the Travel Book (Seyahat-Name) of Evliya Çelebi - Ayhan Dever (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Sport lodges are institutions that are responsible for providing athletes with accommodation, food and training. Sport lodges had the same tasks as today's sports clubs and played a vital role in the institutionalization and development of sports within the borders of the Ottoman Empire. Evliya Çelebi is a prominent 17th century traveler. During his lifetime, he traveled throughout the Ottoman Empire and compiled in his 10-volume Seyahatname (Travelogue) what he saw, experienced and heard throughout his journeys. Objectives. The aim of this study was to trace in Evliya Çelebi's Seyahatname the sport lodges established in the Ottoman Empire. The general structure of sport lodges was addressed based on Evliya Çelebi's notes in Seyahatname. Methods. A literature review was conducted and the parts of Seyahatname describing sport lodges were screened and analyzed. Moreover, books on Turkish Sport History were examined and additional information was presented. Results. Evliya Çelebi's Seyahatname mentions three sport lodges established in Bursa, Edirne and Istanbul but makes no reference to other sport lodges established especially in Anatolia. The analysis of Seyahatname shows that sport lodges can be regarded as the world's first sport museums. Conclusion.It is recommended that further studies be conducted to investigate sport lodges in more detail.